Research on the Relationship Model between Professional Identity and Life Meaning of Clinical Medical Freshmen based on Artificial Intelligence Medical Image Detection. (29th June 2022) - Li, Xiufeng; Li, Ping; Gao, Yaxuan; Wang, Tan; He, Ying; Li, Xinhui
Abstract : Objective . To understand the current situation of professional identity and life significance of clinical medical freshmen in a university in Xinjiang, analyze its influencing factors, find out the influencing factors and causes, and intervene and improve them. Provide the public with better medical and health management services, so that people can independently and effectively predict and prevent diseases; at the same time, it can also guide people to make more correct and wise choices in uncomfortable situations. Methods . A questionnaire survey was conducted on 793 freshmen majoring in clinical medicine with the college students' professional identity questionnaire and the Chinese version of the meaning in life scale (C-MLQ). Results . The freshmen total score of professional identity was (97.48 ± 12.21). The total score of meaning in life was (53.26 ± 7.15), and the meaning in life and the professional identity were significantly positively correlated ( r = 0.467, P < 0.01 ). Students with first choice, only child, urban living, and parents with a high educational level scored higher in their professional identity P < 0.05 . First choice ( β = −0.11, P < 0.001 ), place of residence ( β = −0.07, P = 0.03 ), father's education level ( β = 0.08, P = 0.04 ), family monthly income ( β = −0.09, P = 0.02 ), and the presence of meaning in life ( β = 0.54, P < 0.001 ) are the influencing factors of students' professional identity. Both professional identity and meaning in life have important relationship with the mental health of medical students. In the development of modern medicine, finding personal career orientation and goals helps to establish a correct outlook on life, values, and the world. It has a positive impact on the development of personal physical and mental health. Conclusion . The professional identity and life meaning of clinical medical freshmen are at the upper middle level, which can be improved through medical education and other measures. The joint efforts of society, schools, families, and individual students are needed to improve the professional identity of medical students.